Ensinando geometria espacial em tempos de cibercultura - Weigel, Mauro (2011)
The teaching of Mathematics, and of Spatial Geometry in particular, is potentially benefited by the technology associated with the Web 2.0 features, especially regarding the possibilities of media integration and interaction between students and the objects of study. Besides the aspect related to resources that can make a methodological approach to teaching and learning, the ease of locating and retrieving information on the Internet allows you to make possible a more contextualized and challenging work. In this sense, we consider the study of concepts related to Spatial Geometry in a perspective that uses the History of Mathematics. The research is supported by theoretical assumptions that the historical context is needed to liven and arouse the interest of the student to relate the content to his daily life. Moreover, it is considered that for effective teaching improvement it is important for a teacher to incorporate technology to the classes. In the search for answers to the research question guiding this work, which sought to see how we could diversify the way Geometry is studied in High School, we developed a teaching method using the History of Mathematics in a blog especially created for this activity. The investigation was conducted with High School students from second grade classes. The content covered, in a sequence of ten activities, is related to the study of the Pyramids, and the background to the historical context could not be timelier: the Pyramids of Egypt. After the development of the activities, all students responded to the survey instrument, where it was possible to record their feelings and opinions about the work done. The work being completed, it was considered that the result was very satisfactory, because there are indicators, from the sensations perceived by the author during the work and later in this analysis, which the proposal methodology allowed the students to have their performance and motivation increased as we supposed to be.